Dark and singular solitons to the two nonlinear Schrodinger equations - Sulaiman, Tukur Abdulkadir; Nuruddeen, Rahmatullah Ibrahim; Mikail, Badamasi Bashir (Elsevier Gmbh, 2019)
In this study, we investigate two nonlinear Schrodinger equations which describe the nonlinear spin dynamics of (2+1)-dimensional Heisenberg ferromagnetic spin chains (HFSC) with bilinear and anisotropic interactions in the semiclassical limit and the dynamics of modulated compressional dispersive Alfven (CDA) waves arising in plasma physics, respectively by using the modified extended tanh expansion method with Riccati differential equation. Dark, singular, combined dark-singular soliton, singular periodic waves and rational function solutions are successfully constructed to the two studied nonlinear models. We give the constraint conditions that validate the existence of the reported soliton solutions. The 2D, 3D, and the contour graphs to some of the obtained solutions are plotted.
Keywords: Ferromagnetic; Compressional dispersive Alfven dark soliton; Singular soliton